Acute Neuromuscular and Hormonal Responses to Power, Strength, and Hypertrophic Protocols and Training Background - Kotikangas, Johanna; Walker, Simon; Toivonen, Sara; Peltonen, Heikki; Häkkinen, Keijo (Frontiers in Sports and Active Living, 2022)
This study investigated how two slightly different athlete groups would differ in acute neuromuscular and endocrine responses to specific resistance exercise loadings and recovery compared to untrained participants. Power athletes (PA, n=8), strength athletes (SA, n=8) and nonathletes (NA, n=7) performed power (PL, 7x6x50% of 1RM), maximal strength (MSL, 7x3x3RM) and hypertrophic (HL, 5x10x10RM) loadings in Smith-machine back-squat. Neuromuscular performance, serum testosterone, growth hormone and cortisol concentrations, and blood lactate (BL) were measured before (Pre), at Mid and after (Post) loading and after recovery for 24 and 48 hours. All loadings led to acute decreases in neuromuscular performance and elevations in hormone concentrations and BL. During PL, a significant group × time interactions occurred in maximal isometric force (F(4,40)=4.189, p=0.006, ηp2=0.295) indicating a greater decrease in PA compared to SA from Pre to Mid (p<0.05), and in countermovement jump height (F(4,40)=2.895, p=0.034, ηp2=0.224) indicating a greater decrease in NA compared to SA from Pre to Mid (p<0.05). During HL, growth hormone was higher in Mid and Post in SA compared to NA (p<0.05). No significant interactions were found during recovery. The differences during PL and HL suggest that the training background may enhance acute responses during the present loadings, whereas it seemed to have a limited effect on the recovery.